Joint stock companies having the local government as sole shareholder – some practical remarks in the case of Romania - Veress, Emõd (The Opole Studies in Administration and Law, 2017)
As a general rule, a joint stock company is based on a contract, therefore at least two shareholders are necessary to establish such a business entity. A sole shareholder joint stock company has an exceptional character, because it can be founded only by the state or by the local government. In the Romanian jurisprudence recently several important problems were raised regarding the operation of sole shareholder joint stock companies, therefore a detailed analysis of the court cases dealing with the representation of the interests of the sole shareholder and with judiciary control over the activity of such companies seems pertinent.